(untitled) (Global Journal of Science Frontier Research, 2014)
Domestic sewage treatment experiments were conducted in trickling filters in laboratory pilot plants in which the peeled dehydrated fruits of Luffa cyllindrica were used as a support medium for microbiological growth, in order to verify its capacity to remove organic matter, measured in terms of Biochemical Oxygen Demand (BOD 5 , 20 ) and Chemical Oxygen Demand (COD). The results obtained, when compared to results from similar pilot plant using stones as supporting medium, indicated that Luffa cyllindrica can substitute, under specific conditions, the traditional support media. Also, although detailed microbiologic studies were not among the objectives of this study, it was observed that the biofilm found in Luffa cyllindrica was richer in species and in a higher evolutive stadium than the biofilm found in the stones. Further studies are recommended.